Exacerbation of Background Nuclear Cataracts in Sprague-Dawley Rats in Embryo-Fetal Development Studies With JNJ-42165279, a Fatty Acid Amide Hydrolase Inhibitor. (August 2021) - van Heerden, Marjolein; Roosen, Wendy; Lachau-Durand, Sophie; Bailey, Graham; Ndifor, Anthony
Fetal examinations in embryo-fetal developmental (EFD) studies are based on macroscopic and dissecting microscopic evaluations, and histopathology is rarely performed other than to confirm macroscopic findings. Fetal lens examination is therefore generally limited to the presence, size, shape, and color of any abnormality. In a Sprague-Dawley rat EFD study with the fatty acid amide hydrolase (FAAH) inhibitor JNJ-42165279, an unusually high incidence of macroscopic granular foci was noted within the lens of gestation day 21 fetuses across all groups including controls, with higher incidence in the high-dose group. On histological evaluation of the lenses from fetuses with/without gross findings, primary lens fiber hypertrophy (swelling) and degeneration were observed across vehicle- and JNJ-42165279-exposed fetuses. In a follow-up study to investigate the progression or resolution of the fetal lens changes, animals exposed to suprapharmacological doses of JNJ-42165279 in utero had higher incidence of nuclear cataracts as detected via slit-lamp ophthalmic examinations on postnatal days 18 to 21 and 35 to 41. No histologic correlates for these cataracts were identified. We conclude that fetal primary lens fiber hypertrophy and nuclear cataracts at ophthalmology, are common background changes in this rat strain that are exacerbated by in utero exposure to the FAAH inhibitor JNJ-42165279.